Bilaminar Chitosan Scaffold for Sellar Floor Repair in Transsphenoidal Surgery - Ramos-Zúñiga, Rodrigo; López-González, Francisco; Segura-Durán, Ivan (Frontiers in Bioengineering and Biotechnology, 2020)
Background: Endoscopic endonasal transsphenoidal surgery (EETS) is a standard technique used to approach sellar tumors. It is relatively safe, minimally invasive and carries a low risk of complications. However, one of the common complications reported with this technique is CSF leakage which causes morbidity, an increase in recovery time and hospital costs. This complication usually occurs from violation of the diaphragma sellae and a defect in the structures of the sellar floor or incomplete repair. In this article we report the first case with the use of a novel bilaminar chitosan scaffold which can be potentially used in the repair of the sellar floor, primarily aiming to the bony part of this structure. Case presentation: After a personalized design employing a tissue engineering strategy, we reconstructed the sellar floor in a 65-year-old woman who had undergone EETS for a pituitary adenoma with progressive bilateral visual loss. To repair the bony defect of the sellar floor, we used a novel bilaminar chitosan scaffold. The patient had an unremarkable postoperative course with no evidence of CSF leak. The polymer was well tolerated without toxicity, infection or complications. After 2 years of follow up the patient remains neurologically intact, and in good endocrinological status. Conclusion: This is the first report of the use of this biomaterial and its biocompatibility in a clinical setting for the repair of the sellar floor during EETS. Our experience with chitosan bilaminar scaffold and in several preclinical studies in the literature have demonstrated good biocompatibility and effective bioengineered bone regeneration due to its excellent osteoconductive properties, this study pretends to be one landmark for further clinical research and larger case series with the use of this personalized tissue engineering materials in order to see they real efficacy to increase the surgeon armamentarium.